(untitled) (Proceedings of International Educators Conference, 2023)
This paper is a project report on the experiment of an English public speaking and debating course with advanced level English majors in College of Arts and Science, Yangtze University. The paper analyzes the validity of the course, introduces the design rationale, the design and experiment process, and students’ responses. The paper suggests that with further development, English public speaking and debating course could be considered as a basic oral training course for advanced-level English majors.